Supramolecular organization of perfluorinated 1H-indazoles in the solid state using X-ray crystallography, SSNMR and sensitive (VCD) and non sensitive (MIR, FIR and Raman) to chirality vibrational spectroscopies. Issue 2 (20th December 2016) - Quesada-Moreno, María M.; Avilés-Moreno, Juan Ramón; López-González, Juan Jesús; Jacob, Kane; Vendier, Laure; Etienne, Michel; Alkorta, Ibon; Elguero, José; Claramunt, Rosa M.
Abstract : The determination of the AC of three perfluorinated 1 H -indazoles that resolve spontaneously as conglomerates. Abstract : 1 H -Indazole derivatives exhibit a remarkable property since some of them form chiral supramolecular structures starting from achiral monomers. The present work deals with the study of three perfluorinated 1 H -indazoles that resolve spontaneously as conglomerates. These conglomerates can contain either a pure enantiomer (one helix) or a mixture of both enantiomers (both helices) with an enantiomeric excess (e.e.) of one of them. The difficulty of the structural analysis of these types of compounds is thus clear. We outline a complete strategy to determine the structures and configurations ( M or P helices) of the enantiomers (helices) forming the conglomerates of these perfluorinated 1 H -indazoles based on X-ray crystallography, solid state NMR spectroscopy and different solid state vibrational spectroscopies that are either sensitive (VCD) or not (FarIR, IR and Raman) to chirality, together with quantum chemical calculations (DFT).